Computational design of a neutralizing antibody with picomolar binding affinity for all concerning SARS-CoV-2 variants. Issue 1 (31st December 2022) - Jeong, Bo-Seong; Cha, Jeong Seok; Hwang, Insu; Kim, Uijin; Adolf-Bryfogle, Jared; Coventry, Brian; Cho, Hyun-Soo; Kim, Kyun-Do; Oh, Byung-Ha
ABSTRACT: Coronavirus disease 2019, caused by SARS-CoV-2, remains an on-going pandemic, partly due to the emergence of variant viruses that can "break-through" the protection of the current vaccines and neutralizing antibodies (nAbs), highlighting the needs for broadly nAbs and next-generation vaccines. We report an antibody that exhibits breadth and potency in binding the receptor-binding domain (RBD) of the virus spike glycoprotein across SARS coronaviruses. Initially, a lead antibody was computationally discovered and crystallographically validated that binds to a highly conserved surface of the RBD of wild-type SARS-CoV-2. Subsequently, through experimental affinity enhancement and computational affinity maturation, it was further developed to bind the RBD of all concerning SARS-CoV-2 variants, SARS-CoV-1 and pangolin coronavirus with pico-molar binding affinities, consistently exhibited strong neutralization activity against wild-type SARS-CoV-2 and the Alpha and Delta variants. These results identify a vulnerable target site on coronaviruses for development of pan-sarbecovirus nAbs and vaccines.